Al-Jużūr al-Muhmalah fī al-Lugah al-‘Arabiyyah - Ahmed Autiyyah Saber (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2020)
The method of collocation innovated by Al-Khalil bin Ahmed indicates that the number of possible binary roots is 756 roots after deleting the repeated one, and the number of possible triple roots is 21.952 roots, the quad is 614.656 roots, and the quintuple is 17.210.368 roots, but the linguistic reality proves that using of these roots is little if What is measured by the neglected ones; The used doesn't add more to the binary than 115 roots, and these roots are structures without derivation, from the triple to 7.198 roots, from the quadrilateral to 3.739 roots, and from the quintet over 295 roots, which means that the Arabs didn't use all the available or possible roots. The ancient linguists tried to explain the use of some roots without some, and to explain the difference in the amount of neglected and used between constructs (double, triple, quadruple, and five buildings). However, the reasons they mentioned didn't rise to the level of statistics to explain all the neglected roots in a way that doesn't allow some of them to deviate from the rule. The research has presented the reasons cited by linguists for neglecting the neglected of the roots, such as the forbidden coalition between some Arab silences, appending the triple to the quadrant, the quadrant to the quintet, the analogy of the transition between the roots with the two roots, and the lack of the need for all the roots. Then the research tried to extract reasons other than those mentioned by linguists, and to know the Sunnah of the Arabs in composing the used roots. What you like, what you deserve, and what you prevent, then the judgment after this is on the neglected roots, a ruling that none of them is deviating from it as much as possible. Among these reasons: the symmetry of the first and second sounds of the root, the similarity of the sounds of one root, the symmetry of the second and the third of the ring sounds, the absence of the correct letters of the root، the preference for “wāw” over the “yā'” in the first position of the root, and the desire of the Arab from other than the three roots. Then the research touched upon an attempt to explain the difference in the amount of the neglected and the used between the twin, triple, quadruple and five buildings, and the great discrepancy between the neglected and used ratios between these buildings.